Dundee ready education environment measure of dentistry: Analysis of dental students' perception about educational environment in college of dentistry, Mustaqbal University - Gurleen Arora (Wolters Kluwer Medknow Publications, 2021)
Introduction: Evaluation of the educational environment is an important element which can be used to improve our curriculum. The aims and objectives of this cross-sectional study were to identify the student's perception about educational environment in College of Dentistry, Mustaqbal University. As the educational environment has a significant impact on the learning and academic performance of the students, the present study will help us identify areas of improvement and refining the dental curriculum. Materials and Methods: A total of 120 students of year 4, 5, 6, and interns, both male and female, responded to the Dundee Ready Education Environment Measure (DREEM) in the 1st month of the second semester, 2021. This scale measures the student's perceptions of the educational environment overall and for five domains: learning, teaching, academic self-perception, atmosphere, and social self-perception. Results: A total of 92 students responded and were generally positive about their learning environment, with a total DREEM score of 130.87 ± 32.73/200. The lowest score for Domain 5 (social self-perception) and the highest score for Domain 1 (student's perception of learning.) were noted. Conclusion: Students' perception of educational environment of College of Dentistry, Mustaqbal University, was more positive than negative. This study provided a valuable insight of how students perceive their course and identified several weak areas that need to be worked upon, hence helping in improvement of the curriculum.